Mammary-like adenocarcinoma of the vulva: a rare case report with next generation sequencing. - Lobrano*, Renato; Manca*, Alessandra; Sini, Maria Cristina; Palmieri, Giuseppe; Petrillo, Marco; Cossu, Antonio; Paliogiannis, Panagiotis (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2023)
Vulvar cancers are rare tumors, representing approximately 5% of gynecological malignancies. Mammary-like adenocarcinomas of the vulva (MLAV) are extremely rare, and their molecular features are poorly described in the scientific literature. We report a case of an 88-years-old woman affected by MLAV with comedo-like features, with a detailed description of the pathological, immunohistochemical and molecular features. Immunohistochemistry (IHC) showed strong staining for Cytokeratin 7, GATA3, Androgen Receptor, GCFPD15, and weak staining for mammaglobin; no staining for Her-2 was found. The proliferation index (Ki-67) was 15%. Molecular testing detected a pathogenic mutation of the AKT1 gene, a likely pathogenic frameshift insertion of the JAK1 gene, and two likely pathogenic frameshift deletions of the KMT2C gene; in addition, two variants of unknown significance (VUS) involving the ARID1A and OR2T4 genes were found. Finally, two CNVs of the BRCA1 gene were identified.